SCIENTIFIC APPROACHES TO DEFINING, REGULATING AND RESEARCHING ENTITY ACCOUNTS RECEIVABLE - Nicolai JIERI; Violeta CODREAN; Ana Carolina COJOCARU (BĂRBIERU) (Eastern European Journal of Regional Studies, 2023)
Abstract. In the process of carrying out economic activities, each entity engages with various business partners, governmental bodies, personnel, and others. Consequently, the relationships formed often result in the emergence of receivables, owing to the time delay in meeting financial obligations related to the sale of economic goods or the provision of advances. The main objective of this research is to comprehensively examine the theoretical aspects related to the concept of accounts receivable, including their definition, classification, and regulation. Additionally, it aims to analyze the normative framework at both the national and international levels, considering economic and legal perspectives. Furthermore, this study encompasses an assessment of scientific productivity, the impact of scientific research, trending topics, and other aspects through bibliometric analysis. It's worth noting that the current market conditions underscore the significance of this research topic, where economic agents have the ability to choose their market and business partners. In this context, accounts receivable play a pivotal role in reflecting the economic and financial situation of both parties involved.